Lógica fuzzy na avaliação da fertilidade do solo e produtividade do café conilon - Silva, Samuel de Assis; de Souza Lima, Juliao Soares; de Souza, Gustavo Soares; de Oliveira, Rone Batista; Xavier, Alexandre Candido (Univ Federal Ceara, Dept Geol, 2010)
The objective of this study was to analyze, using the geoestatistic and a system of classification fuzzy, the fertility of an experimental area with base in chemical attributes of the soil and its relationship with the productivity of the conilon coffee. The study was accomplished in the experimental farm of the INCAPER - ES. The soil samples were collected in the depth of 0 - 0.2 m, being analyzed the attributes: matches, potassium, calcium and magnesium, aluminum, sum of bases, cation exchange capacity (pH 7), and saturation percentage. The data were submitted to a descriptive, exploratory, and geostatistical analysis. A system of fuzzy classification was applied using the attributes described to infer about the fertility of the soil and its relationship with the productivity of the culture. The fertility possibility presented positive spatial relationship with the productivity of the culture, with higher values of this where the possibility of fertile soil is superior.
Fuzzy logic for evaluation of the fertility of soil and productivity of conilon coffee
Keywords: Coffea canephora Pierre x Froenher; Fertility of the soil; Coffee growing; Geostatistics